2014
DOI: 10.3892/mmr.2014.2684
|View full text |Cite|
|
Sign up to set email alerts
|

microRNA-335 inhibits proliferation, cell-cycle progression, colony formation, and invasion via targeting PAX6 in breast cancer cells

Abstract: microRNAs (miRNAs) have been demonstrated to play crucial roles in tumorigenesis. However, the molecular mechanism underlying the roles of miRNAs in breast cancer remains largely unknown. In this study, we showed that miR-335 is downregulated in a number of breast cancer tissues and cell lines. Luciferase reporter assays identified the paired box 6 gene (PAX6) as a novel target of miR-335. Further investigation revealed that miR-335 negatively regulates the expression of PAX6 in human breast cancer MCF-7 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…Furthermore, it has been established that deregulated PAX6 is involved different types of human cancer, including non-small cell lung cancer (16), retinoblastoma (17), glioma (18), colorectal cancer (19), prostate cancer (20) and breast cancer (21). Meng et al (21) demonstrated that miR-335 inhibited cell cycle progression, colony formation, proliferation and invasion by targeting PAX6 in breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been established that deregulated PAX6 is involved different types of human cancer, including non-small cell lung cancer (16), retinoblastoma (17), glioma (18), colorectal cancer (19), prostate cancer (20) and breast cancer (21). Meng et al (21) demonstrated that miR-335 inhibited cell cycle progression, colony formation, proliferation and invasion by targeting PAX6 in breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, the detailed molecular mechanisms responsible for BC cell invasion remain unclear. Recently, miRNAs have emerged as an important mechanism responsible for BC cell invasion (29,30). In this study, we demonstrated that the expression levels of miR-214 were upregulated in BC tissues compared with adjacent benign tissues.…”
Section: Discussionmentioning
confidence: 63%
“…As a member of the miRNA, miR‐335‐5p is widely reported as a pivotal molecule in various cell processes, especially in tumors, such as cell differentiation, proliferation, apoptosis, migration and invasion . The target genes of miR‐335‐5p include RAS p21 protein activator 1 (RASA1) in gastric cancer, paired box 6 (PAX6) in breast cancer, BCL2 like 2 (BCL2L2) in renal carcinoma, poly (ADP‐ribose) polymerase1 (PARP‐1) in small cell lung cancer and ROCK1 in osteosarcoma . The results of the current study revealed that ROCK1 3′UTR had the binding site for miR‐335‐5p by using bioinformatics prediction (TargetScan).…”
Section: Discussionmentioning
confidence: 76%